Islamic Boarding Schools-Based Educational Quality Management At Madrasah Aliyah Banyuwangi - Manda Syahri; St. Rodliyah; Zainal Abidin (JIEMAN: Journal of Islamic Educational Management, 2023)
Educational quality management is an activity of planning, implementing, controlling and supervising all work activities that must be completed to maintain the quality desired by formal institutions under the auspices of Islamic boarding schools. This study focuses on discussion on: How to plan, implement, evaluate. The purpose of this study is to describe the planning, implementation, and evaluation of the quality of pesantren-based education at MA Al-Amiriyah. This study used a qualitative approach with a case study type, data collection techniques using passive participatory observation methods, semi-structured interviews and documentation. The data obtained were then analyzed using a descriptive analysis model with interactive Miles Huberman and Saldana namely: data collection, data condensation, presenting data and drawing conclusions. As well as the validity of the data using source triangulation, technical triangulation and member checks. The results of this study are: (1) planning the quality of pesantren-based education at MA Al-Amiriyah. (a) formulate program priorities including content standards, graduate competency standards, process standards and teaching staff qualification standards. (b) formulate the goals to be achieved. (2) the implementation of quality education based on Islamic boarding schools at Madrasah Aliyah Al Amiriyah. (a) meet the standard needs of educators. (b) implementation of tasks in accordance with fields and functions. (3) evaluating the quality of pesantren-based education at MA Al-Amiriyah. (a) supervision of school programs or activities (b) reports on the implementation of activities. (c) evaluation of the learning process. Manajemen mutu pendidikan merupakan kegiatan perencanaan, pelaksanaan, pengendalian dan pengawasan semua aktivitas kerja yang harus diselesaikan untuk mempertahankan mutu yang diinginkan lembaga formal yang berada dibawah naungan pondok pesantren. Penelitian ini memfokuskan pada : Bagaimana perencanaan, pelaksanaan, evaluasi Mutu Pendidikan berbasis pesantren di  MA Al-Amiriyah. Adapun tujuan dari penelitian ini Mendeskripsikan  perencanaan,  pelaksanaan, evaluasi Mutu Pendidikan berbasis pesantren di  MA Al-Amiriyah. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus, teknik pengumpulan data menggunakan metode observasi partisipasi pasif, wawancara semi terstruktur dan dokumentasi. Data yang diperoleh kemudian dianalisis menggunakan model analisis deskriptif dengan interaktif Miles-Huberman dan Saldana yaitu: pengumpulan data, kondensasi data, menyajikan data dan menarik kesimpulan. Serta keabsahan data menggunakan triangulasi sumber, triangulasi teknik dan member check.Hasil penelitian ini adalah: (1) perencanaan mutu pendidikan berbasis pesantren di Madrasah Aliyah Al-Amiriyah. (a) merumuskan prioritas program diantaranya standar isi, standar kompetensi lulusan, standar proses dan standar kualifikasi tenaga pendidik. (b) merumuskan tujuan yang ingin dicapai. (2) pelaksanaan mutu pendidikan berbasis pesantren di Madrasah Aliyah Al-Amiriyah. (a) memenuhi kebutuhan standar pendidik. (b) pelaksanaan tugas sesui dengan bidang dan fungsi. (3) evaluasi mutu pendidikan berbasis pesantren di Madrasah Aliyah Al Amiriyah. (a) supervisi program atau kegiatan sekolah (b) laporan pelaksanaan kegiatan. (c) evaluasi pada proses pembelajaran.